2018
DOI: 10.1002/chem.201804392
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Assisted Back Energy Transfer in Luminescent TbIII Complexes for Thermosensing Properties

Abstract: A luminescent TbIII complex with a hexafluoroacetylacetone (hfa) ligand shows a characteristic back energy transfer (BEnT), which leads to high temperature sensitivity and potential application as a thermosensitive paint. Ligand‐assisted BEnT was observed when a phosphine oxide ligand was introduced into Tb(hfa)3 complex, which was shown to affect the activation energy (ΔEa) and frequency factor (A) in the BEnT process between TbIII ion and hfa ligands. According to temperature‐dependent emission‐lifetime meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 42 publications
2
39
0
Order By: Relevance
“…The calculated activation energy E a at around room temperature was 3.6×10 3 cm −1 . This calculated parameter is similar to that of thermo‐sensitive [Tb(hfa) 3 (tppo) 2 ] at room temperature ( E a =3.0×10 3 cm −1 ) . The Arrhenius analysis indicates that the BEnT from Eu III to the T 1 state should be activated at room temperature.…”
Section: Figuresupporting
confidence: 71%
See 1 more Smart Citation
“…The calculated activation energy E a at around room temperature was 3.6×10 3 cm −1 . This calculated parameter is similar to that of thermo‐sensitive [Tb(hfa) 3 (tppo) 2 ] at room temperature ( E a =3.0×10 3 cm −1 ) . The Arrhenius analysis indicates that the BEnT from Eu III to the T 1 state should be activated at room temperature.…”
Section: Figuresupporting
confidence: 71%
“…We herein select an Eu III coordination compound attached with triphenylene units for the back energy transfer (BEnT) process. The BEnT process with activation energy of the luminescence could be a key point for construction of a novel time‐resolved O 2 ‐analysis . In our previous study, an Eu III complex with triphenylene phosphine‐oxide, [Eu(hfa) 3 (dppto) 2 ] (hfa: hexafluoroacetyl‐acetonate, dppto: 2‐diphenylphosphoryl‐triphenylene), had a long T 1 lifetime on a low‐lying energy level (20,490 cm −1 ) .…”
Section: Figurementioning
confidence: 99%
“…On the other hand, an emission-lifetime-based temperature detection system has been focused for precise and distinguishable analysise ven under luminescents urfaces. [13][14][15][16][17] Carlos et al described an emission-lifetime-based thermometer with aw ide temperature range (12-320 K) using BEnT from the Eu III ion to 9-fluorenone-2,7-dicarboxylic acidl igands in the Eu III -MOF. [13] We have demonstrated that BEnT is strongly influenced by indirect long-range ligand-ligand electronic couplings (LECs)i n Tb III coordination polymers (Figure1a).…”
Section: Introductionmentioning
confidence: 99%
“…[13] We have demonstrated that BEnT is strongly influenced by indirect long-range ligand-ligand electronic couplings (LECs)i n Tb III coordination polymers (Figure1a). [14] Lanthanide coordination polymers showl ifetimes in the sub-millisecond range, which are longert han those of organic molecules, transition metal complexes,a nd semiconductor nanomaterials. The long emission lifetime makes it possible to time-gate out any background fluorescencefrom luminescent surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation